Resveratrol Prevents Cataract Formation by Inhibiting Pro-inflammatory Mediator-induced Dysregulation of Lens Calcium - R. Manikandan (Journal of Ophthalmic Science, 2020)
The effect of resveratrol, a free radical scavenger, during cataract development was evaluated in the Wistar rat pup model. This study investigated the possible free radical scavenging potential of resveratrol at 40 mg/ kg body wt dose in selenite-induced cataract in rat pups. Intraperitoneal injection of sodium selenite (15 µm mol/ kg body wt) in 8 to 10 day old rat pups lead to severe oxidative stress in the tissues evidenced by decreased antioxidants and increased lipid peroxidase, nitric oxide, superoxide anion, hydroxyl radical generation, inducible nitric oxide synthase (iNOS) as well as nuclear factor kappa B (NF-kB) expression levels that probably led to cataract formation. Selenite exposure also caused an increase in total calcium in the eye lens and significantly inhibited the activity of Ca2+ ATPase but not Na+/ K+ ATPase or Mg2+ ATPase. However, both pre- and co-treatments with resveratrol, but not post-treatment, led to an increase in antioxidant levels with a concomitant reduction in oxidative stress and also rescued the selenite-mediated increase in lens Ca2+ and inhibition of Ca2+ ATPase activity in the eye lens. The results of this study demonstrate antioxidants decrease and increase in free radical generation triggered by selenite causes the inactivation of lens Ca2+ ATPase leading to a rise in intracellular Ca2+ level. Resveratol treatment was able to prevent selenite-induced oxidative stress and in turn the inhibition of lens opacification. Thus, resveratrol has the potential to function as an anti-cataractogenic agent, possibly by preventing free radical-mediated accumulation of Ca2+ in the eye lens.
Keywords: Cataract